Comparison of All-Polyethylene Tibial Versus Metal-Backed Tibial Component in Total Knee Replacement Surgery - Farooq Azam Khan, Waqas Ali, Bilal Ahmad Abbas, Khalid Mehmood, Nisar Ahmed, Talha Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Total knee replacement (TKR) is the most successful procedure in Orthopedics. The selection of an ideal implant relies on better survivorship, restoration of functional activities and cost-effectiveness. This study compared the effectiveness of all-polyethylene (AP) versus metal-backed tibial (MTB) implant in TKR patients in terms of objective and subjective patient related outcomes. Objectives: To compare the effectiveness of all-polyethylene tibial implants versus metal-backed tibial implants in total knee replacement patients in terms of improvement in the American Knee Society Score (AKSS). Methodology: It was a nonrandomized controlled trial done in the Orthopaedic Department of the Sharif Medical City Hospital, Lahore, after approval by the institutional ethical committee. Fifty patients of grade IV knee joint osteoarthritis for greater than six months were included by nonprobability convenient sampling technique. The patients were allocated equally into standard treatment and intervention groups; patients underwent TKR with MTB implants in the standard group and AP implants in the intervention group after taking informed written consent. The AKSS score was calculated pre-operatively, 3 months and 6 months after surgery by the team member not involved in surgical planning. Results: A statistically significant improvement was observed in pre-operative to post-operative knee scores (p-value = 0.004) and functional scores (p-value = 0.001) with TKR. When the means of knee scores were compared between AP and MTB implants, there was no significant difference between the two groups between pre-operative and post-operative knee scores and functional scores. Practical implication Conclusion: There is no significant difference in knee score between the all-polyethylene and metal-backed implants regarding pain and functional status. All-polyethylene implants are a better substitute for MTB implants due to their cost-effectiveness, particularly in countries with financial constraints. The most practical implication of the current study is health economics. In a developing country with a low per capita income, expensive implants can be swapped with low cost implants to bring the cost of the procedure down. Keywords: All-polyethylene tibial, Metal-backed tibial, Total knee replacement, American Knee Society Score, AKSS.